PENERAPAN TEKNOLOGI HITUNG IKAN PADA PETANI LELE DI DESA KADILANGU KEC. KANGKUNG KAB. KENDAL - Unang Achlison; Budi Hartono; Khoirur Rozikin; Sulartopo Sulartopo (Elkom : Jurnal Elektronika dan Komputer, 2019)
Production of freshwater fish farming (ponds) in Kangkung Subdistrict in 2015 reached 4.42 tons or valued at 97.19 million rupiah and the condition is growing more and more. The number of fish seeds is measured conventionally by observing the senses of the eye and causing inaccurate (inaccurate) measurement results. This study offers a solution for counting fish by using a microcontroller based phototransistor technology. Phototransistor has a linear function of the received light intensity that is flowing current (ON) and if there is a condition of light intensity blocked by fish passing through it then the current does not flow (OFF). The trial results of the fish seed count tool have an accuracy of 97% so that it can be used by fish farmers.